2018
DOI: 10.6000/1929-4409.2018.07.05
|View full text |Cite
|
Sign up to set email alerts
|

Geography and Sentencing: Does Country of Citizenship Influence Sentence Longevity?

Abstract: Contentious debates on immigrants in the United States has led to growing interest in their treatment in the criminal justice system. Much of what is known, however, springs from research that treats immigrants as a homogeneous group. The lumping of all immigrants into one category potentially mask variances in sentencing based on national origins. The current study disaggregates federal sentencing data to explore whether length of sentence differs by the defendants' geographical region of citizenship. After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…2. There are several noteworthy studies that have begun to explore differences in citizenship effects at sentencing across national origins (Holland 2017;Iles and Adegun 2018;Logue 2009;Orrick and Piquero 2015). However, these studies have generally focused on a single, specific national origin (e.g., Mexican only) or a single type of offense (e.g., drug offense only).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…2. There are several noteworthy studies that have begun to explore differences in citizenship effects at sentencing across national origins (Holland 2017;Iles and Adegun 2018;Logue 2009;Orrick and Piquero 2015). However, these studies have generally focused on a single, specific national origin (e.g., Mexican only) or a single type of offense (e.g., drug offense only).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…According to numerous studies, sports selection is one of the most important factors for achieving sports results (Volkov & Filin, 1983;Seluyanov & Shestakov, 2000;Sergienko, 2013;Gale Iles et al,, 2018). Naturally, various sports use different methods and criteria for sports selection.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has shown that citizenship status played a significant role in sentence severity. Additionally, Sentence severity for Hispanic females may be attributed to negative portrayals of them as dangerous and raising gang members; thus, judges may have perceived them as more blameworthy in contributing to the “drug problem” in the United States (Albonetti, 1997; Brennan, 2006; Crow & Kunselman, 2009; Iles & Adegun, 2018). Finally, judges may view Hispanic females who were in the country legally and participating in illegal drug activity as abusing their “privilege” of being in the United States (Lynch, 2016).…”
Section: Discussionmentioning
confidence: 99%